Analysis of Contact Force and Deflection in Drop Weight Impact of Abaca Fiber Sandwich Composite with Aluminum Alloy Using Finite Element Method - Al-Afkar, Haris (Journal of Engineering and Science, 2024)
The study simulates a drop weight impact test on sandwich composite materials composed of abaca fiber with an aluminum honeycomb core, utilizing the Finite Element Method (FEM) via Ansys LS-DYNA 2023 R1 software. The specimen model adheres to ASTM D7136 standards, incorporating variations in fiber orientation (woven, unidirectional, random) and impactor velocities of 1 m/s, 2 m/s, 2.43 m/s, and 3 m/s. Simulation outcomes reveal that at 1 m/s, the random orientation exhibited the highest deformation at 2.36 mm, compared to 1.96 mm for woven and 2.06 mm for unidirectional. At 3 m/s, deformation increased markedly, with random reaching 7.54 mm, unidirectional 5.61 mm, and woven 5.07 mm. The unidirectional orientation recorded the highest peak contact force at 3 m/s, reaching 3800 N, followed by woven and random. Energy absorption escalated with velocity, peaking at 17 J for unidirectional at 3 m/s. The contact force versus deflection curves indicate a penetration failure mode across all specimens. Fiber orientation significantly influences structural resistance to impact, with unidirectional excelling in peak force resistance and random demonstrating superior energy absorption through deformation.